Method of static stability dominant identification - Zhen Hu; Ting Cui; Yuanhang Dai; Daojun Chen; Dan Yang; Yating Li (IET Generation, Transmission & Distribution, 2023)
Abstract Two extreme cases of static stability are voltage stability and power angle stability. The general stability analysis only focuses on one of the voltage stability or power angle stability. The stability limit and state change are studied for a certain kind of stability characteristics. In this paper, the stability limits of static voltage and power angle are derived, respectively. Therefore, different stability characteristics and their interrelationships can be further studied. The index to judge the dominant stability characteristic is defined. The proposed index only needs the system wide‐area measurement information to quickly and accurately judge the dominant static stability characteristics. The dominant instability (DI) characteristic index proposed in this paper is equal to 1 or −1, which can help to quickly identify whether the power angle stability or voltage stability is dominant. The effectiveness of the method is proved by a simple system.